Forensic pathology diagnostic: isolation of small non-coding rna apt amers against soluble cell surf ace gl ycoprotein cd54 - Thergarajan, Pera Vina (Universiti Sains Malaysia, 2016)
One of the primary responsibility for forensic pathologist, is to assess the wound vitality. Generally, they apply the knowledge of immunohistochemical analysis instead of molecular knowledge in identification of the wound vitality. Currently, monoclonal antibody was widely used for the diagnosis of wound vitality by detecting CD54 antigen which is responsible for mediating immune and inflammatory responses. However, this immunohistochemical analysis was practiced very limitedly due to the laborious and expensive production of monoclonal antibody. Therefore, this issue overcomes by the isolation pool of aptamers against soluble cell surface glycoprotein CD54. In this study, small pool of non-coding RNA aptamers was successfully isolated against soluble cell surface glycoprotein CD54 by using SELEX technology. The isolation of pool of RNA aptamers began from optimization of library, in vitro selection and analysis of binding activity with the selected target. The binding activity between the isolated aptamer and the target protein was evaluated by enzyme-linked oligonucleotide assay (ELONA). The maximum binding activity can be observed from aptamer isolated from 11th cycle and it shows the highest absorbance value up to 0.362 nm in average. The aptamer isolated from this study, has the potential to be used as high affinity ligands for the capture and subsequently determination of wound vitality and eventually can be used as an alternative for monoclonal antibody in immunohistochemical process.